Molecular characterization of MMP-9 gene in Murrah buffaloes by reverse transcription- polymerase chain reaction (RT-PCR) - PANDIYAN, GURU D V; KRUPAKARAN, R PRAKASH; BALAMURUGAN, T C; ARUNKUMAR, S; PERUMAL, P (The Indian Journal of Animal Sciences, 2015)
Matrix metalloproteinase -9 (MMP-9) is one of the most important metalloproteinases involved in degradation of cellular matrix during several physiological as well as pathological process including ovulation, fertilization, implantation and parturition. A study was conducted to confirm the presence of MMP-9 gene in blood samples of Murrah buffalo cows at different reproductive physiological stages. Healthy Murrah buffalo cows (18), aged about 3–6 years was divided into 3 groups, each group consisting of 6 animals, viz. pregnant (group 1), oestrous (group 2) and anoestrous (group 3) buffalo cows were selected. Experimental animals were managed and fed as per the farm schedule. Blood samples were collected in vacutainer containing sodium citrate and the blood samples were transferred immediately to the laboratory and were stored at –20°C in deep freezer till further use. Total RNA was isolated from the blood samples and reverse transcription- polymerase chain reaction (RT-PCR) was carried out. Primers targeting catalytic domain of the MMP-9 was designed. The total cellular RNA was obtained from 500 μL of blood was 0.108 μg and the concentration of the RNA was 0.216 μg/mL. The ratio of A260/A280 was 1.81 indicating that isolated RNA was reasonably pure. RT-PCR was carried out in 2 steps as and the first step was to synthesize cDNA and the second step to amplify the desired genes from cDNA by PCR. The RT-PCR products were subjected to 1% agarose gel electrophoresis and the expected sizes of 1080 bp for catalytic domain was observed in all the three groups of Murrah buffalo cows.